'n Kontrastiewe beskouing van tweetalige woordeboeke in Suid-Afrika en Japan - Sakurai, Takashi; Kotzé, Ernst F. (Lexikos, 1997)
A Contrasting View on Bilingual Dictionaries in South Africa and JapanBoth dictionaries that combine Afrikaans and African languages and dictionaries that combine Japanese and Western languages incorporate unrelated languages. In this respect lexicographers in Japan and South Africa have the potential for fruitful cooperation. Nevertheless, major differences between bilingual dictionaries in South Africa and Japan came to the fore during the transforming of the Afrikaans/Zoeloe-woordeboek (Afrikaans / Zulu Dictionary) of Kotzé and Wela into an Afrikaans-Japanese dictionary. Differences in microstructure include the use of phonetic transcriptions, indication of the distinction between transitive and intransitive verbs, the ordering of example-sentences and the use of certain symbols as aids. The difference in social context is reflected in the choice of sensitive lexical items and the size of the dictionaries. These differences had to be accounted for in the remaking.The remaking of existing dictionaries is an approved method in Japanese lexicography and there are some historical examples of this practice. However, this does not merely entail a shift of target language but also adapting the structure of the dictionary to the conventional format acceptable to the users (in this case Japanese speakers). Bilingual dictionaries in South Africa that fall under the same typological category as the Afrikaans-Japanese dictionary (in treating genealogically unrelated languages) can benefit from the comparison made in this article.Keywords: abusive lexical items, afrikaans, bilingual dictionary, example-sentences, japanese, labelling, learner's dictionary, macrostructure, microstructure, ostensive dictionary, phonetic transcription, transculturalisation, transitivity, translation equivalent